Handling and mapping geographic information - Cunty, Claire; Mathian, Hélène (ISTE Ltd, 2025)
With the increasing proliferation of data and the systematization of geographic information referencing, maps are now a major concern - not only for specialists, but also for urban planning and development organizations and the general public. However, while producing a map may seem straightforward, the actual process of transforming data into a useful map with a specific purpose is characterized by a series of precise operations that require knowledge in a variety of fields: statistics, geography, cartography and so on. Handling and Mapping Geographic Information presents a wide range of operations based on a variety of examples. Each chapter adopts a different approach, explaining the methodological choices made in relation to the theme and the pursued objective. This approach, encompassing the entire map production process, will enable all readers, whether students, researchers, teachers or planners, to understand the multiple roles that maps can play in the analysis of geographical data.
Description based on online resource; title from digital title page (viewed on October 15, 2024)
Keywords: Cartography; Cartographie; cartography (discipline)